A Practitioner's Guide To Intergovernmental Fiscal Transfers - Shah, Anwar, 1948- 1948- (The World Bank, 2006)
Intergovernmental fiscal transfers are a dominant feature of subnational finance in most countries. They are used to ensure that revenues roughly match the expenditure needs of various orders (levels) of subnational governments. They are also used to advance national, regional, and local area objectives, such as fairness and equity, and creating a common economic union. The structure of these transfers creates incentives for national, regional, and local governments that have a bearing on fiscal management, macroeconomic stability, distributional equity, allocative efficiency, and public services delivery. This paper reviews the conceptual, empirical, and practice literature to distill lessons of policy interest in designing the fiscal transfers to create the right incentives for prudent fiscal management and competitive and innovative service delivery. It provides practical guidance on the design of performance-oriented transfers that emphasize bottom-up, client-focused, and results-based government accountability. It cites examples of simple but innovative grant designs that can satisfy grantors' objectives while preserving local autonomy and creating an enabling environment for responsive, responsible, equitable, and accountable public governance. The paper further provides guidance on the design and practice of equalization transfers for regional fiscal equity as well as the institutional arrangements for implementation of such transfer mechanisms. It concludes with negative (practices to avoid) and positive (practices to emulate) lessons from international practices